Dual energy 4D-CT of parathyroid adenomas not clearly localized by sestamibi scintigraphy and ultrasonography – a retrospective study. Issue 124 (March 2020) - Woisetschläger, M.; Gimm, O.; Johansson, K.; Wallin, G.; Albert-Garcia, I.; Spångeus, A.
Highlights: Diagnostic accuracy of parathyroid adenoma could be enhanced using dual-energy CT. Dual-energy CT from real non-contrast scans could help in equivocal cases. Lower energies showed greater HU differences in spectral analysis. Abstract: Purpose: At present, the gold standard for diagnosing PAs includes ultrasonography of the neck and sestamibi scans of the parathyroid. The objective of this study was to evaluate scans performed in 4D-DECT (4D-dual-energy mode) at three different time points, in order to analyze spectral information from PAs, lymph nodes (LNs), and thyroid gland (Thy). Method: Fifteen patients (mean age: 57 ± 18.9 years) with primary hyperparathyroidism, in which previous ultrasound and sestamibi scanning proved to be negative or equivocal, underwent 4D-DECT in three different phases. Hounsfield units (HU), dual-energy information (electron density [Rho], atomic number [Z], dual-energy index [DEI]), and spectral information (keV) were determined. Results: For all energies, PAs exhibited significantly lower HU-values than the Thy in non-contrast images, and higher HU-values than LNs in the arterial phase (p < 0.05). All three tissues differed significantly in HU in the venous phase at 90 kV, 150 kV, and mixed 0.8 images; the Thy showed significantly higher HU-values than PAs or LNs in non-contrast images at 90 kV, 150 kV, mixed 0.8 images, and [Rho] (p < 0.05). LNs exhibited significantly lower HU-values than PAs and Thy in the arterial phase at 90 kV, 150 kV, mixed 0.8, Rho, Z, and DEI (p < 0.05). With regards to spectral information, lower energies showed greater HU differences between the three tissues. During the venous phase, there were significant differences between all three tissues up to 100 keV (p < 0.05). Conclusions: We identified significant differences in HU-values and spectral information between PAs, LNs, and Thy at different energies and contrast phases.